Sheet Metal 2023 - Merklein, Marion; Hagenah, Hinnerk; Duflou, Joost; Fratini, Livan; Evangelista Martins Prado, Gustavo Marcondes; Meschut, Gerson; Micari, Fabrizio (Material Research Forum, 2023)
The book presents recent advances in the following areas: High speed cutting and forming of sheet metals, Incremental forming, Joining by forming, Material characterization, Modelling, Presses and press tools, Processes, Quality and reliability, Sustainabili